2020
DOI: 10.1186/s12941-020-00399-3
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo infection of murine precision-cut lung tissue slices with Mycobacterium abscessus: a model to study antimycobacterial agents

Abstract: Background Multidrug-resistant infections due to Mycobacterium abscessus often require complex and prolonged regimens for treatment. Here, we report the evaluation of a new ex vivo antimicrobial susceptibility testing model using organotypic cultures of murine precision-cut lung slices, an experimental model in which metabolic activity, and all the usual cell types of the organ are found while the tissue architecture and the interactions between the different cells are maintained. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 63 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…Some bacteria, like Trueperella pyogenes, only appear to infect animals but not humans, with their pathogenic effects having been studied in PCLS [48]. Additional studies in PCLS studied Mycobacterium tuberculosis [49], Mycobacterium abscessus [50], Yersinia pestis [51], and Staphylococcus aureus [52] to understand the pathologic features of infection and agents used to treat these infections. Additionally, co-infection of PCLS with influenza and a Mycobacterium strain showed that the influenza infection increased the susceptibility to Mycobacterium infection by attenuating responses to the bacteria that would otherwise allow the animal to clear the bacteria [53].…”
Section: Studies In Infectious Diseasementioning
confidence: 99%
“…Some bacteria, like Trueperella pyogenes, only appear to infect animals but not humans, with their pathogenic effects having been studied in PCLS [48]. Additional studies in PCLS studied Mycobacterium tuberculosis [49], Mycobacterium abscessus [50], Yersinia pestis [51], and Staphylococcus aureus [52] to understand the pathologic features of infection and agents used to treat these infections. Additionally, co-infection of PCLS with influenza and a Mycobacterium strain showed that the influenza infection increased the susceptibility to Mycobacterium infection by attenuating responses to the bacteria that would otherwise allow the animal to clear the bacteria [53].…”
Section: Studies In Infectious Diseasementioning
confidence: 99%
“…It was found that in Mycobacterium abscessus infections, lesions in the tissue structure or inflammatory infiltration in the alveolar lumen were observed 24–48 h after infection, while animal models required at least 10 to 60 days for lung injury to occur [ 48 , 61 ]. Different types of mice have different infectivity and relative drug resistance, leading to inconsistent results in vivo [ 62 , 63 ].…”
Section: Application Of Pcls Technology In Various Respiratory Inflam...mentioning
confidence: 99%
“…The process of PCLS generation preserves most features of the native lung tissue, that is, its architecture and mechanical properties (Hiorns et al., 2016 ; Pybus et al., 2021 ) as well as a complex cellular composition, including resident lung cells, for example, fibroblasts, ATI and ATII epithelial cells, and immune cells, for example, macrophages, monocytes, and NK and T cells (Stegmayr et al., 2021 ). Neutrophils have been detected in murine PCLS (mPCLS) (Akram et al., 2019 ; Molina‐Torres et al., 2020 ) but considering that they are short‐lived ex vivo and that the PCLS are disconnected from blood and lymphatic circulation, their number is highly dependent on the way PCLS are generated and for how long slices are kept in culture. The absence of immune cell recruitment can be exploited to define the response of resident cells to infection and treatment.…”
Section: Pcls: a Near Native Lung Environment To Study Airway Biologymentioning
confidence: 99%
“…Mycobacterium abscessus (MAb) is a fast growing NTM and imminent multidrug‐resistant health threat for patients with respiratory conditions such as COPD and cystic fibrosis (CF) (Molina‐Torres et al., 2020 ). Upon infection of mPCLS, progressive tissue damage occurred, for example, alveolar edema, vascular congestion, and extravasion of lymphocytes and erythrocytes in the septa and alveolar spaces with rupture and thickening of alveolar septa by 48 hr post infection, concomitantly with infiltration of histiocytes, aggregates of foamy macrophages, and fragmentation of polymorphonuclear cells (Molina‐Torres et al., 2020 ). MAb were found in macrophages and type I and II pneumocytes.…”
Section: Pcls As Model For Human Respiratory Infectious Diseasesmentioning
confidence: 99%